قضايا النقد في كتاب الممتع في صنعة الشعر - المياحي، عادل عبدالكاظم جويد (كلية الإمارات للعلوم التربوية, 2018)
يشكل كتاب الممتع في صنعة الشعر لعبد الكريم النهشلي إطلالة مبكرة للتفكير النقدي في المغرب العربي، فقد مثل أنموذجا لحصيلة المستوى النقدي والأدبي العربي، فالنهشلي ولد بالمحمدية وترعرع في القيروان التي شهدت نهضة فكرية وأدبية في عهد الصنهاجيين، وأضحت ملتقى الرحالة والمهاجرين، وحصيلة التلاقح الفكري بين المشرق والمغرب، وهذا كله كان له عظيم الدور في صقل شخصيته، ففضلا عن بصيرته النقدية، كان شاعرا مجيدا، مقدما عارفا بأيام العرب وأشعارها، وقد أرسى دعائم بناء كتابه الممتع على غرار النقد المشرقي، فقد حاول النهشلي محاكاة ما تداوله النقاد آنذاك من قضايا نقدية كانت تشغل فكر الناقد العربي، كمفهوم الشعر والقديم والحديث واللفظ والمعنى، والمفاضلة بين الشعر والنثر والسرقات الشعرية، وغيرها من القضايا النقدية، وقد حاول جاهدا إيجاد لمسة نقدية للتراث المغربي تكون إيذانا لإبداع مصنفات نقدية أكثر أصالة وعمقا، فضلا عن جمعه لكثير من النصوص الشعرية التي يرفد بها منهجه وتفكيره النقدي، وما يحبذ للشاعر في ضوء ذلك أن يبدي تمسكه بالمنهج الفني والأخلاقي في شعره.
Al-Momtee in the work of poetry for Abdul-Karim al-Nahshali is an early form of critical thinking in the Arab Maghreb. It represented a model for the outcome of the Arab monetary and literary level. He was born in Muhammadiyah and grew up in Kairouan, which witnessed a renaissance of thought and literature during the Sinhajis era. Orient, and Morocco, and all this was a great role in refining his personality, as well as his critical insight, was a glorious poet, in advance familiar with the days and notices of the Arabs, has laid the foundations of building his book interesting like the Oriental criticism, This was one of the critical issues that preoccupied the Arab critic, such as the concept of poetry, the old, the modern, the literal and the meaning, the trade-off between poetry, prose, poetry thefts and other monetary issues. He tried hard to find a critical touch of Moroccan heritage that would allow us to create more authentic and profound works of cash, Of the poetic texts that lend his method and critical thinking, and what is favored by the poet in light of that show his attachment to the artistic and moral approach in his poetry.
Keywords: كتاب: الممتع في صنعة الشعر -- النهشلي، عبدالكريم -- الفكر النقدي -- المغرب العربي -- النقد العربي -- التراجم